After completing the first step of applying the distributive property to the equation \( 4 + 2(1 + x) = 12 \), we need to distribute the \( 2 \) across the terms in the parentheses.
Let's perform the distribution:
\[ 2(1 + x) = 2 \cdot 1 + 2 \cdot x = 2 + 2x \]
Now substituting this back into the equation gives us:
\[ 4 + 2 + 2x = 12 \]
Now, combine the constants on the left side:
\[ 6 + 2x = 12 \]
So, after completing the first step using the distributive property, the equation becomes:
\[ 6 + 2x = 12 \]